Pharmacotherapy of Acute Lymphoblastic Leukemia in Pediatric Patients: A Review of Efficacy and Adverse Effects - Agrawal, Amit; Bhargava, Naina (Indian Journal of Child Health, 2024)
Acute Lymphoblastic Leukemia (ALL) is a hematological malignancy highly prevalent in children. B-cell ALL is characterized by uncontrolled proliferation of B lymphoblasts, which impairs normal hematological function and causes clinical symptoms such as persistent fever, bone pain, swollen lymph nodes, petechiae, pallor, and bruising. The therapy for pediatric ALL encompasses four main approaches: surgical intervention, immunotherapy, radiotherapy, and chemotherapy. Despite numerous medical advances over the years, only a few drugs have been approved for pediatric ALL. This review focuses on the mechanisms of action, efficacy, and adverse effects of pharmacotherapeutic agents that have been used to manage pediatric ALL over the years, such as vincristine, asparaginase, anthracyclines, 6-mercaptopurine, methotrexate, cyclophosphamide, cytarabine, and glucocorticoids. The review also highlights significant aspects of the prevalence of ALL in pediatric populations, the influence of genetics on ALL occurrence, and the fundamentals of treatment regimens. Survival rates in pediatric ALL are significantly higher compared to other malignancies; however, the treatment has a wide range of adverse effects that affect the patient’s quality of life during and post-treatment. Treatment options such as immunotherapy, stem cell transplantation, targeted therapy, gene modification, and novel drugs are constantly evolving and offer the potential for better management, especially in high-risk groups. Although the rate of remission and full recovery after treatment is quite high in pediatric ALL, the search for more effective and less toxic therapies remains a top priority, especially in cases of disease relapse.